PRESSURE INJURIES IN ADULTS AND THE ELDERLY: A SCOPING REVIEW - Fecchio, Carolina Amadeu; Tanoue, Mariana Kato; Dias, Jhenicy Rubira; Mansano, Victória Adryelle Nascimento; Luz, Kelly Cristina Suzue Iamaguchi; Radovanovic, Cremilde Aparecida Trindade; Rodrigues, Thamires Fernandes Cardoso da Silva (Cogitare Enfermagem, 2024)
Objective: to map the evidence available in the literature on the development and characteristics of pressure injuries in adults and the elderly in primary and tertiary care settings. Method: retrospective analytical scoping review, carried out in 2023, in the Virtual Health Library, PUBMED, EMBASE, Web of Science, and SCOPUS databases. Registration (DOI 10.17605/OSF.IO/C63YM). Results: 29 studies were selected. The lesions were predominantly stage 2, located in the sacral, gluteal, and calcaneal regions, which developed during hospitalization, and some had recurrent lesions. Granulation tissue, liquefaction necrosis, and/or coagulation were found in the wound bed, with epithelialized, macerated, or a flaky edge. The presence of exudate was rarely reported. Conclusion: Based on these results, care can be improved by understanding the characteristics of pressure injuries, investing in therapies that optimize the healing process, improving patients’ quality of life, and reducing the cost of wound care.